2022
DOI: 10.3389/fcell.2022.895856
|View full text |Cite
|
Sign up to set email alerts
|

VAP Proteins – From Organelle Tethers to Pathogenic Host Interactors and Their Role in Neuronal Disease

Abstract: Vesicle-associated membrane protein (VAMP)-associated proteins (VAPs) are ubiquitous ER-resident tail-anchored membrane proteins in eukaryotic cells. Their N-terminal major sperm protein (MSP) domain faces the cytosol and allows them to interact with a wide variety of cellular proteins. Therefore, VAP proteins are vital to many cellular processes, including organelle membrane tethering, lipid transfer, autophagy, ion homeostasis and viral defence. Here, we provide a timely overview of the increasing number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 219 publications
2
8
0
Order By: Relevance
“…1a ) 1 , 5 , 6 . One well-established ERMCS tether is the ER-localized Vesicle-associated membrane protein (VAMP)-associated protein B (VAPB) 13 15 , which interacts with mitochondrial binding partners to facilitate calcium and lipid transfer 16 , 17 and can harbour mutations that cause a severe form of motor neuron disease 18 , 19 . The best characterized binding partner for VAPB in the mitochondria is the outer mitochondrial membrane (OMM) component, protein tyrosine phosphatase interacting protein 51 (PTPIP51) 14 , 16 , 20 .…”
Section: Mainmentioning
confidence: 99%
“…1a ) 1 , 5 , 6 . One well-established ERMCS tether is the ER-localized Vesicle-associated membrane protein (VAMP)-associated protein B (VAPB) 13 15 , which interacts with mitochondrial binding partners to facilitate calcium and lipid transfer 16 , 17 and can harbour mutations that cause a severe form of motor neuron disease 18 , 19 . The best characterized binding partner for VAPB in the mitochondria is the outer mitochondrial membrane (OMM) component, protein tyrosine phosphatase interacting protein 51 (PTPIP51) 14 , 16 , 20 .…”
Section: Mainmentioning
confidence: 99%
“…The increased appreciation of interorganelle interactions in recent years has unveiled a variety of MCSs in eukaryotes 39 . These closely apposed and tethered membranes facilitate numerous cellular processes, making them prime candidates for microbial control or mimicry 9,10 . Thus far, examples of pathogenic subversion of MCSs have been limited to interactions between eukaryotic membrane compartments [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that ER-mediated MCSs are susceptible to pathogen subversion 9,10 . Pathogens appear to either manipulate pre-existing MCSs 4 or establish new ones between the ER and the host-derived membrane that harbors the pathogen 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens employ intricate strategies to co-opt host cell machinery and manipulate cellular metabolism to ensure their survival and replication. Recent studies have revealed the pathogen’s ability to modify host inter-organelle communication (Kors et al, 2022; Jiang et al, 2022). Upon host cell entry, certain obligate intracellular bacteria adopt a unique endocytic membrane-bound vacuole, referred to as the Bacteria-Containing Vacuole (BCV), to evade the host immune response and support bacterial replication (Santos and Enninga, 2016; Petit and Lebreton, 2022).…”
Section: Introductionmentioning
confidence: 99%